Plasma methionine metabolic profile is associated with longevity in mammals - N. Mota-Martorell (Nature Portfolio, 2021)
Mota-Martorell and colleagues use a comparative metabolomics approach to examine plasma metabolite levels associated with methionine metabolism in 11 mammalian species. They identify species specific plasma profiles indicative of a link between lifetime longevity and methionine metabolism.